MENA financial markets - Maghyereh, Aktham (Managerial finance ;, 2007)
Even though most Middle-Eastern and North African (MENA) countries have embarked on economic reform and structural adjustment programs, the Asian crisis of 1997 shifted the focus of such programs to financial markets. However, the lack of institutional development is a powerful obstacle to an increased access to MENA capital markets. Additionally, the region witnessed, and still, wars, political turmoil and economic instability. Consequently, MENA countries have not yet emerged as economic powers, which might explain the lack of academic research on MENA capital markets. In fact, it is unclear.